Bisphenol A and di(2-ethylhexyl) phthalate exert divergent effects on apoptosis and the Wnt/-catenin pathway in zebrafish embryos: A possible mechanism of endocrine disrupting chemical action - ALTURFAN, EBRU IŞIK (SAGE PUBLICATIONS INC, 2017)
Polyethylene terephthalate (PET) and polycarbonate (PC) are the most commonly used plastics in water bottles. Di(2-ethylhexyl) phthalate (DEHP) is used as a plasticizer in PET plastics, and bisphenol A (BPA) is used to produce PC. Both DEHP and BPA are known for their potential endocrine disrupting effects. The Wnt/-catenin signaling pathway has important roles in cell proliferation, cell specification and cell fate determination during embryonic development. Recent reports suggest a link between the Wnt/-catenin signaling pathway and apoptosis. The aim of this study was to investigate the relation between Wnt/-catenin signaling and apoptosis in the case of BPA and DEHP exposure in zebrafish embryos. Accordingly, in vivo cell death was assessed using acridine orange staining, and reverse transcription polymerase chain reaction was used to determine the expressions of wnt3a, gsk3 and ccnd1. Proliferative cell nuclear antigen, -catenin and Wnt3a expressions were determined immunohistochemically. Vitellogenin levels were determined using Enzyme Linked ImmunoSorbent Assay (ELISA). Increased vitellogenin levels, apoptosis, and wnt3a and gsk3 expressions were observed in BPA-exposed zebrafish embryos. Increased apoptosis in the BPA-exposed embryos may be due to the pro-apoptotic changes induced by Wnt3a, whereas DEHP might be suggested to have a minor effect as Wnt3a expression; vitellogenin levels and apoptosis did not increase significantly following exposure to DEHP.
Keywords: Di(2-ethylhexyl) phthalate; bisphenol A; apoptosis; Wnt; -catenin; zebrafish embryo; GLYCOGEN-SYNTHASE KINASE-3-BETA; EXPOSURE; CELLS; PROLIFERATION; ACTIVATION; EXPRESSION; TOXICITY; GENE; RATS